1996
DOI: 10.1291/hypres.19.83
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dimorphism of Renal .ALPHA.2-Adrenergic Receptor Regulation in Dahl Rats.

Abstract: Male Dahl salt-sensitive hypertensive (S) rats develop hypertension faster than females. We measured renal a2-adrenergic receptor density of inbred Dahl salt-sensitive (SSIJR) and salt-resistant (SR/JR) rats, using [3H]-rauwolscine saturation binding studies. Male and female SSIJR rats were gonadectomized or sham-operated at 6 weeks of age and fed a high salt diet for 4 weeks. Additional intact SSIJR and SRIJR rats of both sexes were fed the high salt diet for a longer period of time (7 weeks instead of 4 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Finally, sex differences in Dahl rats have been reported (204,437,754); however, none of these addressed thick ascending limb function.…”
Section: Dahl Ratmentioning
confidence: 99%
“…Finally, sex differences in Dahl rats have been reported (204,437,754); however, none of these addressed thick ascending limb function.…”
Section: Dahl Ratmentioning
confidence: 99%
“…Several experimental studies also lend support to gender differences in the regulation of the a2-adrenoceptor and its relation to blood pressure. Indeed, in normotensive and hypertensive rat models, male compared with female animals had a higher blood pressure and an elevated a2-adrenoceptor density in the kidneys [24,25]. Castration of male spontaneously hypertensive rats reduced the malefemale differences in blood pressure and the renal a2adrenoceptor density by 60% [24].…”
Section: Alcohol Intake Menopausementioning
confidence: 99%
“…Alpha 2A receptors in the kidney have also been implicated in hypertension [31,[75][76][77]. In SHR and Dahl hypertensive rats renal alpha 2 receptor density, as assessed by radioligand binding studies, was greater in males than females [31,78]. In contrast, we observed that renal alpha 2A receptor expression was decreased in male compared to female SHR.…”
Section: Discussionmentioning
confidence: 49%